STANDARDS OF TEXTUALITY IN COMPARABLE TEXTS: THE GREAT DEPRESSION IN TWO TEXTBOOKS - Nazarov , Asilbek (Scientific practical conference, 2026)
The research paper is supposed to utilize a text-linguistic framework by the help of comparative analysis to juxtapose two textbooks about the Great Depression. The research relies on Robert de Beaugrande and Wolfgang Dressler's standards of textuality. The study covers not only constructions and historical background of the texts but also meanings between lines and target audience of each genre precondition their linguistic and structural choices. Through a systematic analysis, the work shows how the US history texts are created by the standards of textuality. The reason why comparative and descriptive methods are taken to use is that there is a need to describe and compare them in order to identify nuances and similarities in terms of cohesion, coherence and readability. There are some factors that directly or inderectly impact on writers consisting of personal attitudes, intertextual factors, socio-economic and political situation. This work reveals how meaning and structure are built differently by different authors and what factors influence genre, structure of texts.